Legal Politics of the Existence of Customary Courts in Civil Procedure Law - Hazar Kusmayanti; Madiha Dzakiyyah Chairunnisa; Dede Kania; Rafan Darodjat (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2024)
Along with the development of increasingly modern globalization, the authority and existence of customary institutions for dispute resolution began to be questioned, especially now that some people tend to resolve their disputes through formal institutions such as state courts and the police. This article examines the legal politics of the existence of customary courts in civil procedure law. The research approach is normative juridic and is analyzed through qualitative juridic, which studies data based on legal aspects. The study's findings indicate that legal discrepancies regarding customary justice in the law of civil events remain. However, there is a history of cooperation between the state and the village courts as regulated in Article 86 letter A, article 103, paragraphs (2) and (3). article 120 letter a and article 135 letter a HIR (KUH Perdata Hindia Belanda). Since the entry into force of Emergency Law No. 1 of 1951, these articles have been abrogated, except for Article 135 letter a HIR. The practical implications of the political study of customary law include adopting a common law recognizing the right to justice for indigenous peoples in Indonesia.